A microfluidic co-culture system to monitor tumor-stromal interactions on a chip - Menon, Nishanth V. (2014)
The living cells are arranged in a complex natural environment wherein they interact with extracellular matrix and other neighboring cells. Cell-cell interactions, especially those between distinct phenotypes, have attracted particular interest due to the significant physiological relevance they can reveal for both fundamental and applied biomedical research. To study cell-cell interactions, it is necessary to develop co-culture systems, where different cell types can be cultured within the same confined space. Although the current advancement in lab-on-a-chip technology has allowed the creation of in vitro models to mimic the complexity of in vivo environment, it is still rather challenging to create such co-culture systems for easy control of different colonies of cells. In this paper, we have demonstrated a straightforward method for the development of an on-chip co-culture system. It involves a series of steps to selectively change the surface property for discriminative cell seeding and to induce cellular interaction in a co-culture region. Bone marrow stromal cells (HS5) and a liver tumor cell line (HuH7) have been used to demonstrate this co-culture model. The cell migration and cellular interaction have been analyzed using microscopy and biochemical assays. This co-culture system could be used as a disease model to obtain biological insight of pathological progression, as well as a tool to evaluate the efficacy of different drugs for pharmaceutical studies.